2007
DOI: 10.1002/anie.200701556
|View full text |Cite
|
Sign up to set email alerts
|

Designing Facial Amphiphiles for the Stabilization of Integral Membrane Proteins

Abstract: General procedure. NMR spectra were recorded on Bruker DRX-500, AMX-500 or AMX-300 instruments. IR spectra were recorded on a Perkin-Elmer 1600 series FT-IR spectrometer. High-resolution mass spectra (HRMS) were recorded on a VG ZAB-ZSE mass spectrometer using MALDI (matrix-assisted laser-desorption ionization) or ESI (electrospray ionization).3α,7α,12α,24-Tetrahydroxycholane (3): [1] To a suspension of LiAlH 4 (3.85 g, 100 mmol) in dry THF (100 mL) at 0°C was added dropwise a solution of cholic acid (15.03 g,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 17 publications
3
103
0
Order By: Relevance
“…We previously reported the synthesis of an FA (hereafter referred to as FA-1) with β-D-maltoside attached to the 7α-and 12α-positions in cholate (16). This unique FA design removed the flexible terminal polar head groups in cholate, CHAPS, and CHAPSO and attached polar side groups under the steroid surface.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported the synthesis of an FA (hereafter referred to as FA-1) with β-D-maltoside attached to the 7α-and 12α-positions in cholate (16). This unique FA design removed the flexible terminal polar head groups in cholate, CHAPS, and CHAPSO and attached polar side groups under the steroid surface.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore the steroid-based facial amphiphiles (FA) are another type of solubilization/stabilization agents being actively developed. They utilize the cholate scaffold, to which (typically) sugar headgroups are attached [82,83]. Such design proved to be useful to not only to stabilize membrane proteins (via tight interactions between a membrane proteins and FA owning to the large hydrophobic surface of the latter), but to also improve their crystallization (via the formation of more compact protein-detergent complexes, which can pack more tightly in a crystal, owing to the ability of FA to mediate intermolecular contacts between molecules of membrane proteins) [84].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…McGregor et al have reported that lipopeptides (LPDs) are self-assembled into a cylindrical micelle with a width similar to that of a lipid bilayer, and further form a rigid sheath around the protein surface [55] . Zhang et al have developed cholate-based amphiphiles that project hydrophilic maltose units from one side of the steroidal skeleton, which is then further developed by the design of "tandem facial amphiphiles (TFAs)" [60,61] . The TFAs contain a pair of maltose-functionalized deoxycholate units, making it long enough to match the bilayer width.…”
Section: Surfactantsmentioning
confidence: 99%
“…These facial amphiphiles are very successful in reducing the micelle size. Both Zhang et al and Chae et al showed that the facial amphiphiles are only approximately 1/6 of the micelle size compared to the traditional detergents such as DDM, with an aggregation number of approximately 37 for FAs and only approximately 6 for the TFAs per PDC [60,61] . Although there is yet to be a direct application of these facial amphiphiles in Figure 3.…”
Section: Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation